Electrographic flow mapping of persistent atrial fibrillation: intra- and inter-procedure reproducibility in the absence of 'ground truth' - Reddy, Vivek Y; Kong, Melissa H; Petru, Jan; Maan, Abhishek; Funasako, Moritoshi; Minami, Kentaro; Ruppersberg, Peter; Dukkipati, Srinivas; Neuzil, Petr (Europace, 2023)
AIMS: Validating mapping systems that identify atrial fibrillation (AF) sources (focal/rotational activity) is confounded by the absence of ground truth. A key concern of prior mapping technologies is spatiotemporal instability, manifesting as poor map reproducibility. Electrographic flow (EGF) employs a novel algorithm that visualizes atrial electrical wavefront propagation to identify putative AF sources. We analysed both intra- (3 min) and inter- (>3 months) procedure EGF map reproducibility. METHODS AND RESULTS: In 23 persistent AF patients, after pulmonary vein isolation (PVI), EGF maps were generated from 3 serial 1 min recordings using a 64-electrode basket mapping catheter (triplets) at right and left atrial locations. Source prevalence from map triplets was compared between recordings. Per protocol, 12 patients returned for 3-month remapping (1 non-inducible): index procedure post-PVI EGF maps were compared with initial EGF remapping at 3-month redo. Intra-procedure reproducibility: analysing 224 map triplets (111 right atrium, 113 left atrium) revealed a high degree of map consistency with minimal min-to-min shifts: 97 triplets (43%), exact match of leading sources on all 3 maps; 95 triplets (42%), leading source within 1 electrode space on 2 of 3 maps; and 32 triplets (14%), chaotic leading source pattern. Average deviation in source prevalence over 60 s was low (6.4%). Inter-procedure reproducibility: spatiotemporal stability of EGF mapping >3 months was seen in 16 of 18 (89%) sources mapped in 12 patients with (re)inducible AF. CONCLUSION: Electrographic flow mapping generates reproducible intra- and inter-procedural maps, providing rationale for randomized clinical trials targeting these putative AF sources.
Keywords: epidermální růstový faktor; Epidermal Growth Factor; Catheter Ablation; Atrial Fibrillation; katetrizační ablace; Treatment Outcome; fibrilace síní; venae pulmonales; lidé; Reproducibility of Results; srdeční síně; reprodukovatelnost výsledků; Panoramic mapping; výsledek terapie; Heart Atria; Humans; Electrographic flow mapping; Basket catheter; Pulmonary Veins; Persistent atrial fibrillation